Insect Management for Cucurbits (Cucumber, Squash, Cantaloupe, and Watermelon) - Susan E. Webb (EDIS, 2005)
Insects and mites can cause severe problems in the production of watermelon, squash, cucumber, and cantaloupe either through direct damage to the crop or through transmission of disease agents, such as the aphid-borne mosaic viruses. Common pests of cucurbits are described in this document. The importance of a particular insect will vary by region and by crop. For example root maggots are more important in North Florida and melon thrips in South Florida. Pickleworm and melonworm rarely attack watermelon. This document is ENY-460, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date August 2001. Revised September 2005.